Policy entrepreneurship and policy networks in healthcare systems - the case of Israel's pediatric dentistry reform - Nissim Cohen; Tuvia Horev (BMC, 2017)
Abstract Background Can the entry of a policy entrepreneur challenge the equilibrium of a policy network and promote changes that might clash with the goals of powerful civil-servants and/or interest groups and, if so, why and how? Our goal is to examine two sides of the same coin: how does an in-depth analysis of Israel's dental care reform enrich our understanding of policy networks and policy entrepreneurship? Second, how does the literature on policy networks and policy entrepreneurship help us understand this reform? Based on a theoretical framework that appears in the literature of policy entrepreneurship and policy networks, we analyze the motivations, goals and strategies of the main actors involved in the process of reforming pediatric dental care in Israel. We demonstrate how a policy entrepreneur navigated within a policy network and managed to promote a reform that, until his appearance, no one else in that network had succeeded in enacting. Methods Our goals are advanced through a case study of a reform in pediatric dentistry implemented in Israel in 2010. It rests on textual analyses of the literature, reports, committee minutes, parliamentary proceedings, print and online media, and updates in relevant legislation and case law between 2009 and 2015. In addition, the case study draws on the insights of one of the authors (TH), who played a role in the reform process. Results Historical circumstances and the Israeli public's longstanding lack of interest in changing the existing model as well as interest groups that preferred the dominance of the private sector in the dental healthcare system kept that area out of the services supplied, universally, under the National Health Insurance Law. This situation changed significantly following the publication in 2007 of a policy analysis that contributed to shifts in the motivations and balance of power within the policy network, which in turn prepared the ground for a policy change. In this environment a determined policy entrepreneur, who identified a window of opportunity, took the lead and instituted an innovative and far-reaching reform. Conclusions A policy entrepreneur can leverage external factors as well as the previous activities of a policy network that has already matured to create a policy change. Such entrepreneurial activity includes maneuvering around opponents and overcoming resistance from various stakeholders.